Directive Speech Acts in Humorous ‘Mop’ Discourse in Papuan Society: A Pragmatic Studies - Mukminin, Muhamad Saiful; Angelita, Tasya (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2023)
This study examines the analysis of the form and function of directive speech acts in the discourse of ‘Mop’ humor in Papuan society. The research method used is descriptive qualitative. The collection technique in this study used linguistic data collection instruments, namely listening techniques, note-taking techniques, and proficient free-involvement techniques. Data analysis in this study consisted of four stages, namely: (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusions and verification. The results of this study indicate that in the discourse of 'Mop' humor in Papuan society there are eight forms and seventeen functions of directive speech acts, namely: (1) Asking has the function of asking, (2) Commanding has the function of commanding, commanding, demanding, instructing, and directing, (3) Ordering has the function of asking and inviting, (4) Recommending has the function of advising, (5) Advising has the function of advising, suggesting, and warning, (6) Permissives has the function of allowing, (7) Prohibitives has the function of prohibiting and limiting, and (8) Requesting has the function of asking and inviting. The most dominant directive speech act used in the discourse of ‘Mop’ humor in Papuan society is the form and function of asking. The existence of a question element in ‘Mop’ implies that communication between speakers and speech partners requires answers to unknown information.